Impact of Veterinary Institutional Access on the Adoption of Scientific Feeding Practices among Women Dairy Farmers in Himachal Pradesh, India - Thakur, Devesh; Ahuja, Rakesh; Sharma, Manoj; Sambyal, Madhu Suman; Dinesh, Krishanender; Khurana, Sanjay Kumar (Indian Journal of Veterinary Sciences and Biotechnology, 2023)
This study evaluates the adoption of scientific animal feeding practices among women dairy farmers in regions with good access to  veterinary institutions. Access to these services is crucial for gender equality, economic empowerment, and sustainable agriculture. But,  such studies are lacking in India. The research involved 150 women farmers in Kangra, Himachal Pradesh, with easy access to veterinary  institutions. High adoption levels were observed for most scientific dairy feeding practices. Colostrum feeding for new-born calves was  the most adopted, while home preparation of animal feed was the least. The study revealed significant correlations between adoption  levels and factors like landholding size, dairy experience, and market orientation. In summary, multiple veterinary institutions’ support  positively influences the adoption of scientific dairy feeding practices among women dairy farmers.
Keywords: Adoption; Dairy farmers; Dairy feeding practices; Veterinary institutions and Women